2010
DOI: 10.1002/eco.184
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration, evapotranspiration and energy fluxes in a temperate wetland dominated by Phalaris arundinacea under hot summer conditions

Abstract: Transpiration, evapotranspiration and evaporative fraction (EF) were measured in a temperate zone wetland dominated by Phalaris arundinacea L. under extremely high temperature and intense irradiation conditions. The infrared (IR) camera recorded no temperature extremes within the stand, indicating that the stand was capable of regulating the overheating by transpiration. The transpiration rate of individual leaves (measured by the gas‐exchange method) was positively correlated with the water vapour pressure de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…Transpiration occurs mostly from the upper leaf surface (Rudescu, Niculescu & Chivu ), reaching up to 7·8 mmol m −2 s −1 (Rejšková et al . ). Water use efficiency based on photosynthesis output and transpiration varies between 4 and 11 μmol (CO 2 ) m −2 s −1 mmol −1 (H 2 O) m −2 s −1 depending on temperature and nutrient supply (Mykleby et al .…”
Section: Structure and Physiologymentioning
confidence: 97%
“…Transpiration occurs mostly from the upper leaf surface (Rudescu, Niculescu & Chivu ), reaching up to 7·8 mmol m −2 s −1 (Rejšková et al . ). Water use efficiency based on photosynthesis output and transpiration varies between 4 and 11 μmol (CO 2 ) m −2 s −1 mmol −1 (H 2 O) m −2 s −1 depending on temperature and nutrient supply (Mykleby et al .…”
Section: Structure and Physiologymentioning
confidence: 97%
“…Although GI systems need not be vegetated, plants and soils can contribute substantially to volume reduction, in particular by enhancing rates of evapotranspiration (ET), interception, and infiltration [6][7][8][9]. Evapotranspiration is arguably the most effective of these processes with respect to volume reduction; studies using weighing lysimeters have found that 50% of incident precipitation can be removed by ET [10][11][12][13][14][15]. Moreover, vegetated GI systems provide additional ecosystem services such as improving air quality and cooling the local environment, thereby promoting human health [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although GI systems need not be vegetated, plants and soils can contribute substantially to volume reduction, in particular by enhancing evapotranspiration (ET), interception, and infiltration (Buccola and Spolek 2011, Lucas and Greenway 2011, Yang andLi 2013, Tu andTraver 2019a). Evapotranspiration is arguably the most effective of these processes; studies using weighing lysimeters have found that 50% of precipitation can be removed by ET (Rejskova et al 2012, DiGiovanni et al 2013, Wadzuk, et al 2013, Wadzuk et al 2015, Zaremba et al 2016, Hess et al 2017. Moreover, vegetated GI systems provide additional ecosystem services such as improving air quality and cooling the local environment, thereby promoting human health (Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%